'Heavy Fog in the Channel. Continent Cut Off'? British Diplomatic Relations in Brussels after 20101. (12th October 2015) - Rasmussen, Maja Kluger
Abstract: What happens when a Member State challenges the unwritten rule of consensual decision‐making in the Council of the EU? Are their diplomats marginalized, or do other countries make an extra effort to attempt to get them on board? In this article, I use the UK (United Kingdom) in the area of financial and economic EU co‐operation as a case study to explore these questions. The British government has been unwilling to sign up for a range of recent EU crisis‐management measures and has not been afraid of utilizing its veto. Based on 33 interviews with diplomats from 20 countries, this article demonstrates that British diplomats have not become marginalized, but changes have occurred; other countries no longer go the extra mile to get the UK on board and they are worried that they will be seen as obstructive if they align themselves with the UK.